1998
DOI: 10.1021/om9804374
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Photolysis of Germatetrasilacyclopentanes

Abstract: The five-membered-ring systems germatetrasilacyclopentanes [R2Si]4GeR‘2 (1) (1a, R = i-Pr, R‘ = Me3SiCH2; 1b, R = i-Pr, R‘ = Ph; 1c, R = t-BuCH2, R‘ = Ph) were synthesized and characterized. The structures of 1b,c have been determined by X-ray crystallography. The Si4Ge rings of 1b,c form an envelope and a distorted half-chair conformation, respectively. The photolysis of 1 using two kinds of light sources (low- and high-pressure mercury lamps) was carried out. The photochemical decomposition of 1a afforded tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Synthesis of 1‐Cyclohexyl‐2,2,3,3,4,4,5,5‐octaisopropyl‐1‐aza‐2,3,4,5‐tetrasilacyclopentane (4a): This compound was synthesized by a method similar to that used for 3a [Scheme , (c)], by treatment of 1,4‐dichloro‐1,1,2,2,3,3,4,4‐octaisopropylcyclotetrasilane11 Cl(R 2 Si) 4 Cl (R = i Pr; 1.4 g, 2.6 mmol) with lithium cyclohexylamide, prepared from cyclohexylamine (0.9 mL, 7.9 mmol in 5 mL of THF) and butyllithium (6.5 mL, 10.2 mmol in hexane). Compound 4a (recrystallized from 2‐propanol): 0.51 g, 35% yield; m.p.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of 1‐Cyclohexyl‐2,2,3,3,4,4,5,5‐octaisopropyl‐1‐aza‐2,3,4,5‐tetrasilacyclopentane (4a): This compound was synthesized by a method similar to that used for 3a [Scheme , (c)], by treatment of 1,4‐dichloro‐1,1,2,2,3,3,4,4‐octaisopropylcyclotetrasilane11 Cl(R 2 Si) 4 Cl (R = i Pr; 1.4 g, 2.6 mmol) with lithium cyclohexylamide, prepared from cyclohexylamine (0.9 mL, 7.9 mmol in 5 mL of THF) and butyllithium (6.5 mL, 10.2 mmol in hexane). Compound 4a (recrystallized from 2‐propanol): 0.51 g, 35% yield; m.p.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 2,2,3,3,4,4,5,5‐Octaisopropyl‐1‐oxa‐2,3,4,5‐tetrasilacyclopentane 6a: This compound was synthesized by a method similar to that used for 5b , by hydrolysis of 1,4‐dichlorooctaisopropyltetrasilane11 Cl(R 2 Si) 4 Cl (R = i Pr; 1.02 g, 1.9 mmol) with H 2 O (3 mL) in THF (7 mL) at 50−60 °C for 15 h. Compound 6a (recrystallized from methanol/ethanol): 0.88 g, 96% yield; m.p. 308−315 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photochemistry of catenated group 14 compounds is of interest since this method can be used to convert one type of catenate to another and also can be used for the generation of reactive intermediates including silylenes, germylenes, stannylenes, and group 14 element centered radical species that can be trapped and characterized . In the case of germanium, the photochemistry of the cyclotrigermane (Mes 2 Ge) 3 has been the most extensively studied and it has been shown that this compound is photochemically converted to a germylene Mes 2 Ge : and a digermene Mes 2 Ge=GeMes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The germadisilaoxetane heterocycle is somewhat deformed with the following bond distances and endocyclic angles: Si-Ge 2. The five-membered germatetrasilacyclopentane ring systems of compounds 23 (R-Pr, f BuCH 2 ) [40,41] were characterized by X-ray analysis. The GeSi 4 heterocycle of these compounds forms an envelope (R-Pr) and a distorted half-chair conformations (R-BuCH 2 ).…”
mentioning
confidence: 99%